Electrochromic Properties of WO3 Thin Film with Various Heat-Treatment Temperature - Kim, Chang-Yeoul; Park, Seok (Asian Journal of Chemistry, 2013)
Tungsten oxide is a representative electrochromic material which has widely researched as an active electrochromic electrode. The electrochromic properties are related with ion intercalation and deintercaltion like lithium or proton ions. So, it is thought that amorphous or crystalline phase of tungsten oxide is very important for the capability and reversiblility of ion intercalation or deintercalaton. In this study, we analyzed the relationships between heat-treatment temperature and electrochromic properties of tungsten oxide film prepared by sol-gel coating method. It is concluded that amorphous phase shows superior intercalation or deintercalation capability to crystalline phase.